2014
DOI: 10.1074/jbc.m114.547331
|View full text |Cite
|
Sign up to set email alerts
|

The 3′–5′ DNA Exonuclease TREX1 Directly Interacts with Poly(ADP-ribose) Polymerase-1 (PARP1) during the DNA Damage Response

Abstract: Background: TREX1 is a 3Ј-5Ј DNA exonuclease, and mutations in human TREX1 are associated with autoimmune/ inflammatory diseases. Results: TREX1 interacts with poly(ADP-ribose) polymerase-1 (PARP1). Conclusion: TREX1 contributes to maintenance of suitable PARP1 levels and its functions in the DNA damage response. Significance: Identification of the molecular mechanism of TREX1 is necessary for understanding the development or progression of TREX1-associated diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 41 publications
(57 reference statements)
2
30
0
Order By: Relevance
“…While TREX1 has not been considered a canonical DNA repair enzyme, recent studies highlight a broader role for this exonuclease. For example, TREX1 has been shown to interact with PARP and facilitates its nuclear localization and activity35. In addition to ssDNA, TREX1 has now been implicated in the degradation of dsDNA and ssRNA3637.…”
Section: Discussionmentioning
confidence: 99%
“…While TREX1 has not been considered a canonical DNA repair enzyme, recent studies highlight a broader role for this exonuclease. For example, TREX1 has been shown to interact with PARP and facilitates its nuclear localization and activity35. In addition to ssDNA, TREX1 has now been implicated in the degradation of dsDNA and ssRNA3637.…”
Section: Discussionmentioning
confidence: 99%
“…TREX1 from humans was reported to be involved in the DNA editing and repairing process. In several studies, it has been shown that TREX1 interacts with DNA polymerases to facilitate the polymerase accuracy [ 21 , 22 ]. Since the silencing of ICP35 gene by dsRNA reduced the viral copy number in the WSSV-infected shrimp, it has been speculated that the role of ICP35 might be involved in viral replication process [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been implicated in the regulation of BER through enhancing PARP1 [poly(ADP‐ribose) polymerase 1] activity. Moreover, TREX1 also possesses exoribonuclease activity and plays a role in the degradation of damaged tRNA substrates . Indeed, a large cohort of BER proteins have been implicated in RNA metabolism, and will be further discussed.…”
Section: Links Between the Ddr And Rna Metabolism Pathwaysmentioning
confidence: 97%